2018
DOI: 10.3389/fimmu.2018.02449
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginyl Endopeptidase (Legumain) Supports Human Th1 Induction via Cathepsin L-Mediated Intracellular C3 Activation

Abstract: Autocrine activation of the complement receptors C3aR and CD46 by complement activation components C3a and C3b produced through C3 cleavage by the protease cathepsin L (CTSL) during T cell stimulation is a requirement for IFN-γ production and Th1 induction in human CD4+ T cells. Thus, lack of autocrine CD46 activation, such as in CD46-deficient patients, is associated with defective Th1 responses and recurrent infections. We have identified LGMN [the gene coding for legumain, also known as asparaginyl endopept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Several studies have shown that it could facilitate cellular proliferation and regeneration by dysregulating mitogenic signaling pathways, sustaining angiogenesis and oncogenesis [30,31]. The internal synthesis and secretion of C3 were observed in various immune cells and GC cells [32][33][34]. Our study confirmed that both SGC-7901 and MGC-803 cell lines produced intracellular C3.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that it could facilitate cellular proliferation and regeneration by dysregulating mitogenic signaling pathways, sustaining angiogenesis and oncogenesis [30,31]. The internal synthesis and secretion of C3 were observed in various immune cells and GC cells [32][33][34]. Our study confirmed that both SGC-7901 and MGC-803 cell lines produced intracellular C3.…”
Section: Discussionsupporting
confidence: 82%
“…LGMN inhibition reduced IFNγ production, CTSL activation and C3a generation in activated human CD4 + T-cells; moreover, CD4+ T-cells from Lgmn-deficient mice showed defective IFNγ production and Th1 induction. 84 CTSS and LGMN also mediate HLA class-II antigen presentation, promoting the generation of competent HLA class-II molecules for peptide binding, 85,86 and processing of exogenous peptides for HLA class-II-presentation, [87][88][89] respectively. CTSS inhibition prevented HLA class-II-mediated antigen presentation in autoimmunity, 90 and reduced the generation of competent HLA class-II and the infiltration of IFNɣ-expressing CD4+ T-cells in a neuropathy model.…”
Section: Discussionmentioning
confidence: 99%
“…In induced regulatory T cells, blocking legumain imparts regulatory function of these cells [112]. Legumain is required for normal Th1 induction in human and mouse CD4 + T cells, through processing of cathepsin L and subsequently cathepsin L-mediated complement C3 activation [113]. Also, legumain can process prothymosin α ( Table 1) into active α1thymosin [78], which is implicated in human CD4 + T cell activation and modulation of cytokine production [114].…”
Section: Functional Roles Of Legumainmentioning
confidence: 99%
“…To proteolytic cleave substrates, prolegumain must be activated. Maturation and stability of legumain, the presence of endogenous inhibitors and/or GAGs, environmental conditions (especially pH and redox potential) and subcellular localization are factors that regulate the legumain activity [27,29,34,113] (Figure 9). In paper I, very low levels of legumain were observed in the cytosolic fraction of both untreated and tunicamycin-treated cells after cell fractionation, showing both glycosylated and unglycosylated legumain in the cytosol.…”
Section: Importance Of Glycosylation For Cellular Localization Of Legmentioning
confidence: 99%